2021
DOI: 10.1111/ppc.12824
|View full text |Cite
|
Sign up to set email alerts
|

From predictions to evidence: Treatment compliance, disease progression and social compliance of patients with schizophrenia in the COVID‐19 pandemic

Abstract: Purpose This study explored how patients with schizophrenia were provided with social support and treatment compliance during the pandemic. Design and Methods A total of 396 patients with schizophrenia and their relatives were interviewed by telephone calls. Findings Multiple antipsychotic use and depot antipsychotics were not superior in preventing relapse. A total of 70.2% of the patients wanted to meet with their psychiatrist online but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Very few participants thought that patients’ distrust or unwillingness to use technology was a barrier to using telepsychiatry. This is consistent with findings from a previous survey in which the majority of patients with schizophrenia reported interest in online meetings with their HCPs, 35 as well as findings from a recent review reporting high acceptance of videoconferencing from participants with schizophrenia-spectrum disorders. 34 Another recent review of 26 studies comparing costs of telepsychiatry services with in-person office visits or usual care for patients with SMIs found that the majority of studies reported telepsychiatry visits to be the less expensive option for patients, primarily due to savings in travel time and expenses and a reduction in lost work time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Very few participants thought that patients’ distrust or unwillingness to use technology was a barrier to using telepsychiatry. This is consistent with findings from a previous survey in which the majority of patients with schizophrenia reported interest in online meetings with their HCPs, 35 as well as findings from a recent review reporting high acceptance of videoconferencing from participants with schizophrenia-spectrum disorders. 34 Another recent review of 26 studies comparing costs of telepsychiatry services with in-person office visits or usual care for patients with SMIs found that the majority of studies reported telepsychiatry visits to be the less expensive option for patients, primarily due to savings in travel time and expenses and a reduction in lost work time.…”
Section: Discussionsupporting
confidence: 91%
“…Since the start of the pandemic, patients, HCPs, researchers, and population health decision-makers have called for an increase in telepsychiatry utilization to ensure continuity of care for patients with SMIs. 35,[37][38][39][40] The current survey findings continue to underscore the need for a hybrid model for patient care, education of patients regarding available treatment options including LAIs for treatment of schizophrenia, and the need for best practice guidelines for telepsychiatry.…”
Section: Discussionmentioning
confidence: 91%
“…Telemedicine proved not to be a barrier to good contact between health professionals and the patients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic significantly impacted the management of patients with chronic diseases. Telehealth and telemedicine are considered inevitable during the COVID-19 outbreak [ 32 , 42 , 43 , 44 , 45 ]. However, Vietnam’s healthcare system, which is accustomed to conventional face-to-face medical management with limited resources, may face many obstacles while shifting toward telehealth and telemedicine.…”
Section: Discussionmentioning
confidence: 99%